2014
DOI: 10.1177/1461444813518183
|View full text |Cite
|
Sign up to set email alerts
|

Being-towards the social: Mood and orientation to location-based social media, computational things and applications

Abstract: Through an investigation of patterns of use of the location-based social network Foursquare derived from an extensive ethnographic survey of users, this paper focuses on the orientation of users towards location-based social media and mobile computational devices. Utilising Heidegger's notions of mood and attunement to the world, the paper argues that the towards-which of the user, that is the mood of the user in a phenomenological sense, is critical to their experience of using location-based social media and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In conclusion we present a new concept of the 'playeur' as being a more suitable method for approaching what impact the use of Foursquare has on the spatial practices of its users. In doing so, this papers builds on the work of Humphreys' (2007;2010) The concept of the 'playeur' makes explicit the temporal-contingent possibilities of locative play with spatial media, and offers that affordance an identity that is congruent with other accounts of understanding place and social ties with LBSNs (Evans, 2014(Evans, , 2015. The 'playeur' is the 'phoneur' who not only employs his or her smartphone to alter how the urban terrain is traversed, but also does so under the auspices of locationbased play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion we present a new concept of the 'playeur' as being a more suitable method for approaching what impact the use of Foursquare has on the spatial practices of its users. In doing so, this papers builds on the work of Humphreys' (2007;2010) The concept of the 'playeur' makes explicit the temporal-contingent possibilities of locative play with spatial media, and offers that affordance an identity that is congruent with other accounts of understanding place and social ties with LBSNs (Evans, 2014(Evans, , 2015. The 'playeur' is the 'phoneur' who not only employs his or her smartphone to alter how the urban terrain is traversed, but also does so under the auspices of locationbased play.…”
Section: Discussionmentioning
confidence: 99%
“…For these participants their movements through the city accordingly became less orientated towards specific locations, and more open to spontaneous adjustment through the digital meditation of play. As a result these participants then found that they were less interested in consuming what these places had to offer (for social capital or other forms of cultural capital, Bourdieu, 1984;Evans, 2014), and more interested in the places themselves, in terms of their symbolism and relation to the game.…”
Section: Locative Play and Spatial Flowsmentioning
confidence: 99%
“…Other scholars have made similar arguments (Evans, 2014: 9; Farman, 2012: 56ff; Frith, 2013: 258). In line with such arguments, Hjorth and Gu in an empirical study of the service Jie Pang (a Chinese equivalent of Foursquare) find that the key motivation for users is ‘to both see where their friends are and to report on new “cool” places’ (Hjorth and Gu, 2012: 703).…”
Section: Introductionmentioning
confidence: 71%
“…The use of check-ins specifically has been found to provide users with new ways of coordinating meetings as well as facilitate chance encounters with friends and to a lesser degree strangers (Humphreys, 2008a, 2008b). It has been suggested that such location sharing may play an important part in the identity construction of users (de Souza e Silva and Frith, 2012, 2013; Farman, 2012; Frith, 2013) and may help them create and maintain social presence and cultivate social capital in networked media (Evans, 2014; Hjorth et al, 2012; Hjorth and Gu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The project described here realized a certain amount of utility in a brutal, instrumental sense: a PhD dissertation, monograph (Evans, 2015a), a major contribution to a co-written book (Evans and Saker, 2017), and several papers (Evans 2011(Evans , 2015bSaker and Evans 2016a, 2016b, 2016c. Given all this material passed through peer review, one can argue that the validity of the project has been established -although that instrumentalist view would be at odds itself with the position on mood and phenomenology as being important in understanding meaning (in location), and so a deeper evaluation is called for in this case.…”
Section: Evaluating the Project As A Contribution To Media Studiesmentioning
confidence: 99%